Strategic Leadership, Person-Job Fit, and Employee Satisfaction: Key Drivers of Organizational Performance at PT. STP: - Situmorang, Soraya Agustina (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study investigated the impact of strategic leadership and person-job fit on employee satisfaction at PT. STP. Utilizing a quantitative-associative approach, the research employed probability sampling and a Likert scale to measure variables. The study demonstrates that strategic leadership has a profound and statistically significant positive effect on employee satisfaction, influenced by the congruence between employees' personal characteristics and job responsibilities. The results show that strategic leadership positively correlates with employee satisfaction, with a regression coefficient of 0.409 and a T-test value of 7.834. Additionally, the person-job fit variable exhibited significant correlations with employee satisfaction, with a regression coefficient of 0.709 and a T-test of 4.103. The study concludes that strategic leadership and person-job fit are crucial factors in enhancing employee satisfaction, ultimately contributing to organizational effectiveness.